Simulação dinâmica do comportamento da transferência de oxigênio em filme ativo multicamada de polietileno tereftalato (PET) para embalagem alimentícia - Thaís Laudares Silva (2023)
The demand for higher quality foods and the need to protect and preserve oxygen- sensitive foods have led to the development of new packaging technologies, such as active packaging. Packaging can be called active when it performs some desired function in food preservation, in addition to providing an inert barrier to external conditions. Plastics are used in food packaging because they offer a wide range of properties. The present work uses as a starting point the study by Di Maio et al., (2017), who developed a one-dimensional (1D) transient diffusion mass transfer model to predict and optimize oxygen barrier performance and physical configurations. of PET (Polyethylene Terephthalate) co-extruded multilayer active films. The film configuration was a three-layer “ABA” type structure where “A” is the inert layer of pure PET and “B” the active inner layer of PET with 10% oxygen scavenger (Amosorb DFC 4020E 880-4020- two). The system of partial differential equations that make up the model of the studied system does not present an analytical solution due to the non-linearity in the kinetic equation, so a solution strategy was used based on the Line Method in which the partial differential equations (PDEs) are converted into a system of ordinary differential equations (ODEs) to be integrated over time. The operational parameters used in the model, as well as their correlations with the system variables, were obtained from the studied literature and estimates, aiming to determine those that best suit the proposed problem. Preliminary results were compared with experimental data from the literature and their evaluation shows similarities, with the sum of squared error 1,7424x10−4. With the optimized parameters, the numerical algorithm under development was implemented for the active monolayer film. And based on the existing models in the literature for the simulation of active packaging, the present work employs two strategies to model the oxygen absorption kinetics with the objective of validating the mathematical model for the film with only an active layer. In both strategies, the parameters of the kinetic model are estimated by minimizing the squares of the deviations of the experimental data, considering the temporal and spatial variation of the oxygen and scavenger concentration in the active layer. The line method is employed to solve the model and the spatial direction is discretized by finite differences. O objetivo de validar o modelo matemático para o filme somente com camada ativa foi alcançado. A taxa de reação é bem descrita pela segunda estratégia proposta no trabalho que apresentou uma diferença mínima de 15,69 entre os valores experimentais e preditos pelos autores de Di Maio et al (2018). Essa estratégia é confirmada como o modelo que melhor se ajusta aos dados experimentais com uma redução significativa de 76% quando comparada ao valor obtido pela primeira estratégia adotada que obteve desvio de 65,2.